Pemanfaatan Bahan Alam Black Garlic untuk Menurunkan Tekanan Darah pada Lansia di Desa Bangun Rejo Kecamatan Tanjung Morawa Tahun 2024 - Dina Afriani; Lisdayanti Simanjuntak; Indra Agussamad; Roy Saputra Berutu; Melin Samosir (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Background: Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a rest/calm state. (Septiyawati, Cahyati and Rustiana, 2021). Purpose: For this reason, this community service activity aims to socialize about the Utilization of Black Garlic Natural Ingredients to Lower Blood Pressure in the Elderly. Method: This community service activity uses the lecture method, and question and answer. The lecture method was carried out by delivering material on the use of Black Garlic. Meanwhile, the question and answer method is carried out by asking participants about the material that has been presented. Results: The results of this community service activity were obtained that participants were able to understand and apply the material that had been delivered. Conclusion: Based on the community service activities that have been carried out, the elderly who are enthusiastic about receiving the entire series of activities starting from the percentage of material to the implementation of the service run smoothly, the elderly are very active in asking questions and answering.